Legal Protection for Workers Experiencing Delayed Wage Payments Without the Imposition of Penalties by Employers - Abditama, Marcel; Farina, Thea; Januardy, Ivans (Journal of Law, Politic and Humanities, 2025)
This study examines the legal protection afforded to workers who experience delayed wage payments without the imposition of penalties on employers, as regulated under Law No. 13 of 2003 on Manpower and Government Regulation No. 36 of 2021 on Wages. The delayed payment of wages constitutes a violation of workers’ rights and may give rise to industrial relations disputes if not addressed effectively. The prevailing legal framework obliges employers—whether through intent or negligence—who delay wage payments to pay a penalty amounting to 5% per day from the fourth to the eighth day of delay, followed by 1% for each subsequent day, up to a maximum of 50% of the wages due. However, many workers are either unaware of their legal entitlements or reluctant to report such violations due to pressure exerted by employers. Using an empirical juridical research method and a qualitative approach involving interviews and field observations, this study aims to: (1) explore the legal protection mechanisms available to affected workers, and (2) identify the obstacles to enforcing sanctions against employers who fail to pay the prescribed penalties for delayed wages